What are the limits of mathematical explanation? Interview with Charles McCarty by Piotr Urbańczyk - McCarty, David Charles; Urbańczyk, Piotr (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2016)
An interview with Charles McCarty by Piotr Urbańczyk concerning mathematical explanation.